PEDAGOGY OF ENCOUNTER: BUILDING RELATIONSHIPS BETWEEN SCIENCE EDUCATION AND CLOWNING - Maués, Ely; Maline, Carla; de Sá, Eliane Ferreira (Seven Editora, 2025)
This article reports on a formative experience conducted in a Pedagogy course. Its objective was to investigate the possible relationships between clowning and science education, identifying how clowning, as an artistic practice, can offer new understandings and transformations in the pedagogical practice of a teacher in the discipline of Methodology of Natural Science Teaching. Starting from a turbulent institutional moment that produced professional discouragement and unease regarding an excessively rational science education training for future pedagogues, the teacher returned to his clown, Melancia, to teach a class. The methodological approach of the research was based on self-study with an emphasis on the narrative of lived experience. The primary data sources for the research were the class notebook for the discipline of Methodology of Natural Science Teaching, offered in the fourth semester of the Pedagogy course, and the initial narrative constructed by the teacher, which was later analyzed and reformulated by the authors of the research. Three lessons emerged from the analysis of this narrative. The first lesson presents vulnerability as a pedagogical virtue and as a foundation for human connection. The second highlights the need to explain to students the pedagogical reasoning that underpins our teaching practices. The third, finally, values enchantment as a constituent element for a more holistic scientific education that values emotions and aesthetic aspects. It concludes that the dialogue between clowning and education offers a fertile ground for rethinking teacher training, promoting a more authentic, human, and sensitive pedagogy, capable of embracing uncertainty and reframing failure as a learning experience.DOI: https://doi.org/10.56238/sevened2025.038-078